PENGARUH PRODUK DAN HARGA TERHADAP KEPUASAN PELANGGAN DALAM MENGGUNAKAN TELKOM SPEEDY DI KOTA SEMARANG - Fadilla, Fitriadewi Nuraini; Rodhiyah, Rodhiyah; Nurseto, Sendhang (Jurnal Ilmu Administrasi Bisnis, 2015)
This research purpose to find out the influence of product and price on the decision satisfaction customers using Telkom Speed. This type of research used is explanatory research, with the samples of as many as 100 respondens. Sample decision uses the purposive sampling technique. The analysis technique uses test validity, test realibility, simple linear regression, multiple linear regression. Result of research and discussion be explained product positive effect on customer satisfaction, which is the better product, the higher the customer satisfaction Telkom Speedy. Price positive effect on customer satisfaction, which is the cheaper the price, the higher the customer satisfaction. There is the influence product effect customer satisfaction, and price effect customer satisfaction.